Influencing Factors of Cross-Border E-Commerce Consumer Purchase Intention Based on Wireless Network and Machine Learning. (8th June 2021) - Lu, Chun-Wei; Lin, Gu-Hong; Wu, Tzu-Jung; Hu, I.-Hsiang; Chang, Yuan-Chieh
Abstract : In recent years, with the continuous development of Internet technology and the deepening of economic globalization, cross-border e-commerce has become a new international trade model and an important growth point of foreign trade. With the popularity of international trade, domestic consumers have a deeper understanding of foreign products and brands and willingness to purchase, but at this stage, cross-border e-commerce transactions are not as close to domestic online shopping, and a few have business opportunities. PortUnity is the first among overseas consumers and some avant-garde consumers with a sense of consumption. Most people have not yet reached real cross-border e-commerce, so cross-border e-commerce has broad development potential on a global scale. As a high-tech field, cross-border e-commerce has few relevant theories and literature. Therefore, this article aims to explore the influencing factors of consumer purchase intention of cross-border e-commerce based on a wireless network and machine learning and to provide decision support for the management and operation of e-commerce in order to promote the better development of cross-border e-commerce. This article analyzes the influencing factors of consumers' intention in cross-border e-commerce shopping by combining literature research and empirical research. With the support of wireless networks and machine learning, perceptual-based ease of use and perceived usefulness of the original TAM, the individual influencing factors of cross-border e-commerce consumers' purchase intention and e-commerce platform factors are summarized according to the characteristics and technology acceptance model of cross-border e-commerce. In this questionnaire survey, the author fully explored the survey value of each respondent, and all the 100 questionnaires were successfully recovered, with a 100% utilization rate of data. The research results of this article show that in addition to the originally perceived usefulness and perceived ease of use, consumers' income level, education level, age, gender, service, safety index and price of cross-border e-commerce platform, and other factors also affect the cross-border consumption frequency of consumers.